In vivo assessment of gastrotomy closure with over-the-scope clips in an experimental model for varicocelectomy - Rolanda, C (2012)
BACKGROUND: Gastrotomy closure remains the major limiting factor for human translation of transgastric surgery; the over-the-scope clip (OTSC) system was proposed as a possibility for this purpose. Transgastric access is good for a pelvic approach, making varicocelectomy a possible indication for natural orifice transluminal endoscopic surgery (NOTES). OBJECTIVE: To evaluate the reliability of the OTSC system in vivo after transgastric testicular vessel ligation (varicocelectomy model). DESIGN: There were 3 experimental groups (5 animals in each): groups 1 and 3, gastrotomy dilation up to 18 mm, surgery was performed with a double-channel endoscope; group 2, gastrotomy dilation up to 13 mm, surgery was performed with a single-channel endoscope. SETTING: Surgical Sciences Research Domain, Life and Health Sciences Research Institute (ICVS), School of Health Sciences, University of Minho, Braga, Portugal. INTERVENTIONS: Bilateral testicular vessel ligation by transgastric access. Gastrotomy closed with the largest version of OTSC system (12 mm): a single clip in groups 1 and 2, and 2 clips in group 3. Animals were monitored for 2 weeks, killed, and submitted for necropsy. MAIN OUTCOME MEASUREMENTS: Adequacy of closure and healing after the use of the OTSC system. Statistical analysis. RESULTS: Vessel ligation was easily achieved in all groups. Although differences in the complication rate did not reach statistical significance (P = .099), there was a clear tendency for a better prognosis in groups 2 and 3 than group 1. In fact, only 2 animals from group 1 had complications related to incomplete gastrotomy closure. LIMITATIONS: Small number of animals per group; nonrandomized study. CONCLUSIONS: The OTSC system was shown to be easy and efficient for gastrotomy closure in a survival experimental model of varicocelectomy, when correctly matching the gastrotomy size with the clip size and/or number.